ChemInform Abstract: Recent Developments Regarding the Use of Thieno[2, 3‐d]pyrimidin‐4‐one Derivatives in Medicinal Chemistry, with a Focus on Their Synthesis and Anticancer Properties. Issue 44 (15th October 2015) - Bozorov, Khurshed; Zhao, Jiang‐Yu; Elmuradov, Burkhon; Pataer, Apar; Aisa, Haji A.
Abstract Review: 91 refs.